Audiovisual Media in the Context of Communicative and Ethical Competences – Media Theology Approach - Małgorzata Laskowska,; Krzysztof Marcyński, (Communication Today, 2025)
The following case study presents the most important references to the transmission of auditive and visual information in the context of communicative and ethical competences that can be found both in the Bible and in the Magisterium of the Church. The authors apply the media theology approach and will show that media theology discipline has its origins in the Bible. The conducted research analyses the Bible-theological sources of using audiovisual media to communicate messages. The goal of the research is an attempt to answer the following questions: How does the Bible refer to the transmission of a word, image, sound and silence? To what extent does the Catholic Church contemporarily carry out the scientific reflection on the audiovisual media and also communicative and ethics competences? How does it fulfil the most important demands of the Second Vatican Council related to this issue? What kind of challenges, regarding the media research, awaits the contemporary theology? Where are the foundations of media theology discipline? The whole article is divided into six sections: the introduction, biblical basis of the visual and auditive transmission, audiovisuality in the teaching of the Church, communicative and ethical competences, media theology – theology of communication, and conclusions.